Exercise & metabolic rate - Stansfeld, J.
1 Exercise may significantly increase metabolic rate for between six and 36 hours after exercise 2 There may be a threshold effect for intensity and duration - possibly 70% VO2max, for 90 minutes or longer 3 Regular endurance exercise may boost levels of activity during the rest of the day 4 Gender seems to be a factor; women's metabolic rates seem less affected by exercise 5 Resistance exercise may be a good way to offset the declining metabolic rate typically found as age increases 6 Going on a strict calorie-restricting diet as well as stepping up exercise may not work as a way of losing weight - you could be better off eating more